2005
DOI: 10.1542/peds.2005-0915
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated Red Blood Cells in Preterm Infants With Retinopathy of Prematurity

Abstract: ABSTRACT. Objective. The aim of this retrospective study was to examine hematologic indices of potential intrauterine hypoxia, including circulating nucleated red blood cells, lymphocytes, and platelets in preterm infants who developed retinopathy of prematurity (ROP) compared with suitable controls. We hypothesized that higher neonatal absolute nucleated red blood cell (ANRBC) and lymphocyte counts and lower platelets would be found in infants who developed ROP, compared with control infants.Methods. Each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…Our data showed no difference in the severity of RDS and ANRBC counts between the two groups [2,3,29] . This indicates that the surfactant therapy and fetal hypoxia were similar in our groups of patients, and contributes little to the development of ROP.…”
Section: Discussioncontrasting
confidence: 64%
“…Our data showed no difference in the severity of RDS and ANRBC counts between the two groups [2,3,29] . This indicates that the surfactant therapy and fetal hypoxia were similar in our groups of patients, and contributes little to the development of ROP.…”
Section: Discussioncontrasting
confidence: 64%
“…Reports by Green et al [4] and Buonocore et al [5] demonstrated that high NRBC counts in neonates were an index of perinatal brain damage. Following their lead, others also reported an association between high NRBC counts and adverse outcomes, including cerebral palsy, periventricular leukomalacia, IVH, and ROP [11][12][13][14][15] . We observed that neonates who, on the day of birth, had NRBC exceeded the 95th percentile for age had fourfold higher odds of developing severe IVH and ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Its main function is erythrocyte maturation and differentiation. 14 Lubetzky et al 15 have shown that neonates with increased absolute neonatal nucleated red blood cells have an increased chance of developing ROP compared with match control and it is possible that rHuEPO contributes to ROP through increased erythropoiesis. Non-erythroid functions of EPO include neurotrophic, neuroprotection, 16 and regulation of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%